Effect of zinc (Zn) on the microstructure and corrosion behaviour of magnesium (Mg) - M. A. F., Romzi; J., Alias; M. I., M. Ramli (Elsevier Ltd, 2021)
In this study, Mg-Zn alloys were prepared by using powder metallurgy technique where magnesium (Mg) and zinc (Zn) were regarded as the starting materials. The effect of Zn towards the microstructure and corrosion behaviour of Mg was studied. The microstructure observation, intermetallic particle distribution, density and X-ray diffraction (XRD) analysis were measured and studied. Besides, the corrosion behaviour of Mg-Zn alloys was observed from hydrogen evolution test and potentiodynamic polarization test. The results showed that due to the same crystal structure of Mg and Zn which was hexagonal close packed (HCP) structure, MgZn2 was formed and complete solid solubility was achieved. The presence of α-Mg and MgZn2 phases was confirmed from the XRD result. The density of the Mg-Zn alloys was increased as the Zn content increased. From the results, Mg-30Zn has the highest value of density compared to Mg-10Zn and Mg-20Zn due to the Zn particles which filled in the gap between the Mg particles. The corrosion test for Mg-Zn alloys showed that Zn addition does improve the corrosion resistance of Mg alloys.